1977
DOI: 10.1080/00288330.1977.9515697
|View full text |Cite
|
Sign up to set email alerts
|

Circulation and hydrology of Manukau Harbour

Abstract: Current meter and current drogue measurements made over tidal periods show that the circulation in Manukau Harbour is mainly tidal, with strongest flows within the inner harbour in the four main channels. In the entrance channel, peak tidal speeds reach 2.25 m.s -1 at the surface, and 0.6 m.s -1 near the bottom. Salinity and temperature observations show that the water is nearly homogeneous with depth in summer. A residence time of 22 d is calculated, assuming the small horizontal salinity contrast is maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 2 publications
2
36
0
Order By: Relevance
“…Several authors have suggested that Wellington Harbour is at least partially isolated from the shelf area immediately outside the harbour entrance (Maxwell 1956, Booth 1975, Harris 1990). The Harbour is a sheltered, well-mixed, nutrient-rich, semi-enclosed body of water (85 km2 in area) with a flushng time of -9 d (Maxwell 1956, Brodie 1958, Booth 1975, Heath 1977. By comparison, the south coast shelf system (Cook Strait) is a high-energy, very exposed coastline.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that Wellington Harbour is at least partially isolated from the shelf area immediately outside the harbour entrance (Maxwell 1956, Booth 1975, Harris 1990). The Harbour is a sheltered, well-mixed, nutrient-rich, semi-enclosed body of water (85 km2 in area) with a flushng time of -9 d (Maxwell 1956, Brodie 1958, Booth 1975, Heath 1977. By comparison, the south coast shelf system (Cook Strait) is a high-energy, very exposed coastline.…”
Section: Discussionmentioning
confidence: 99%
“…Boccardia syrtis), while predictable with flushing is relatively high as a result of the fact that a regard to the annual timing of their occurrence, were large proportion of the Harbour is emptied at every unpredictable in terms of their magnitude. Large low tide (Heath 1975, Heath et al 1977 The prevailing wind direction over Manukau Hardia syrtis interactions inhibit the recruitment of PI. lilbour is from the southwest and west in all seasons, iana and have contributed to the low abundances of winds from the northeast are not uncommon (Fig.…”
Section: Evaluation Of Community Persistence and Variabilitymentioning
confidence: 99%
“…85 km 2 ), linked in the south to coastal Cook Strait via a single channel. Mean water depth of the harbour is 14 m, with a maximum depth of 32 m south-west and south-east of Matiu-Somes Island (Heath 1977). Tides are semi-diurnal and small with a maximum amplitude of 1.5 m.…”
Section: Methodsmentioning
confidence: 97%